SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF ADEFOVIR DIPIVOXIL IN BULK AND TABLETS - CHARUSHILA H. BHIRUD,; SHIVANAND N.HIREMATH, (International Journal of Pharma and Bio Sciences, 2013)
Two simple, rapid, sensitive and accurate UV- Spectrophotometric and first order derivative methods have been developed for estimation of Adefovir in bulk and tablets. In methanol: water (3 :7), the λmax of Adefovir was found to be 260 nm and the same spectrum was derivatized into first order derivative using UV probe software of instrument (shimadzu 2450), at âˆ†λ = 2. The amplitude of the trough was recorded at 273 nm. In both these methods, linearity was observed in the concentration range of 4 – 32 µg/mL. The assay results of both these methods were in good agreement with label claim. The methods were validated statistically and recovery studies.